Prevalence, risk factors, quality of life, and awareness of MASLD among Egyptian university students: a cross-sectional study - Mohamed El-Kassas; Marwa Romeih; Abobakrelsedik Fangary; Ali Abouelyazeed; Islam Abdelfattah; Aya Alerian; Ahmed Ekbal; Yosra Abdelsalam Elshaikh; Samar Abbas; Marwa Tahoon; Hanaa Nagdy; Mohamed Elbadry (Egyptian Liver Journal)
Abstract Background Metabolic dysfunction-associated steatotic liver disease (MASLD) is a leading cause of liver-related morbidity and mortality. Despite very high predictive estimates, the actual disease prevalence and other epidemiological characteristics among Egyptians still need to be determined. This study aimed to investigate the prevalence of MASLD, its related risk factors, awareness, and patient-reported outcomes among university students in Egypt. Methods In this cross-sectional study, abdominal ultrasound was used to detect liver steatosis, followed by assessing other cardiometabolic risk factors to diagnose MASLD. The awareness level of the participants about MASLD and its risk factors was investigated using a specifically designed questionnaire. Additionally, we assessed healthy lifestyle determinants with a special questionnaire and used the Multidimensional Fatigue Inventory (MFI) score to measure the participants' fatiguability. Results Three hundred fifty university students have been recruited in this study (204 females and 146 males, mean age 20.3 ± 1.7 years). MASLD diagnosis was made in 45 participants (12.9%; 19.9% in males and 7.8% in females). Gender and BMI were positively associated with MASLD risk factors. Among students with MASLD, 57.8% were overweight or obese, compared to 38.4% of those in the healthy and underweight groups, with a statistically significant difference (p = 0.013). Only 34.7% of the participants demonstrated adequate MASLD awareness (score ≥ 5/9), indicating substantial knowledge gaps. Conclusion MASLD is moderately prevalent among Egyptian university students. Unhealthy lifestyle, lack of exercise, and Westernized dietary habits were the major risk factors for MASLD. Special attention should be paid to modifying MASLD contributing risk factors and raising disease awareness through channels such as digital platforms and medical curricula is crucial.